2004
DOI: 10.1037/0893-3200.18.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Timing Is Everything: Pre-Engagement Cohabitation and Increased Risk for Poor Marital Outcomes.

Abstract: Data from a longitudinal study were used to examine differences among couples that cohabited before engagement, after engagement, or not until marriage. Survey data and objectively coded couple interaction data were collected for 136 couples (272 individuals) after engagement (but before marriage) and 10 months into marriage. At both time points, the before-engagement cohabiters (59 couples) had more negative interactions, lower interpersonal commitment, lower relationship quality, and lower relationship confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(202 citation statements)
references
References 28 publications
(42 reference statements)
11
187
2
2
Order By: Relevance
“…Such "trial marriages" (Bennett, Blanc, and Bloom 1988) involve relatively low investment and are therefore easier to terminate; unsuccessful partnerships are effectively "weeded out" (Cherlin 1981;Klijzing 1992). Indeed, most young adults appear to believe that cohabitation improves the chances of a subsequent marriage (Kline et al 2004), suggesting that lay people's views about premarital cohabitation concur with this theoretical perspective.…”
Section: Premarital Cohabitation and Divorcementioning
confidence: 54%
See 1 more Smart Citation
“…Such "trial marriages" (Bennett, Blanc, and Bloom 1988) involve relatively low investment and are therefore easier to terminate; unsuccessful partnerships are effectively "weeded out" (Cherlin 1981;Klijzing 1992). Indeed, most young adults appear to believe that cohabitation improves the chances of a subsequent marriage (Kline et al 2004), suggesting that lay people's views about premarital cohabitation concur with this theoretical perspective.…”
Section: Premarital Cohabitation and Divorcementioning
confidence: 54%
“…However, duration of prior cohabitation was not found to influence subsequent marital instability by Lillard, Brien, and Waite (1995) -short cohabitations appeared to offer no advantage compared to longer cohabitations. More recently, Kline et al (2004) showed that those who are engaged at the point when the couple starts cohabiting are at much less risk of subsequent marital break-up. Hence, commitment to the relationship appears to be an important aspect influencing later partnership success (Stanley and Markman 1992).…”
Section: Premarital Cohabitation and Divorcementioning
confidence: 99%
“…Scores ranged from 4 to 28, with higher scores representing greater confidence. Cronbach's alpha for the short form in this study was α=0.96, a higher internal reliability than studies that used the 10-item scale (Kline et al, 2004;Whitton et al, 2007).…”
Section: Confidence In the Marriagementioning
confidence: 67%
“…This process can lessen the danger of having an unhappy marriage that eventually ends in divorce. Thus, young people view pre-marital cohabitation as a means of improving their chances in future marriage, and of "divorceproofing" their relationship (Manning and Cohen 2012;Kline et al 2004;Thornton and Young-DeMarco 2001). Cohabitation is therefore frequently conceptualized as a "trial marriage" or a "testing period" before marriage (Heuveline and Timberlake 2004;Seltzer 2000;Kiernan 2004).…”
Section: Literature Overview: Freedom In Cohabitationmentioning
confidence: 99%